EVALUASI KEBIJAKAN PERLINDUNGAN KONSUMEN PRODUK MAKANAN DAN MINUMAN TERHADAP ZAT PEWARNA TERLARANG DI KABUPATEN PROBOLINGGO - Natsir, Mohammad (JUMANJI (JURNAL MANAJEMEN JAMBI), 2019)
The purpose of this study was to determine consumer protection food and drink product against illegal coloring substances the judged less successfull because the presence of food and drink containing substances forbidden coloring is still outstanding in the markets and consumed by the public. The method used is to with the CIPP Model, namely the evaluation context, input, process and product. Context analysis to perform a test of whether the  objectives are formulated clearly and specifically, or not.  Evaluasi input to do the test if input to achieve adequateas well as how its quality. The evaluation  process is related to how the procedure doing the program, and if there are a weakness in support of the work process. Evaluation of Products related to the evaluation of results achieved from a program or policy, as well as whether the program needs to be continued,followed by revision or not followed. This research is qualitative research, evaluation research with qualitative design-verivikatif, with variants of the qualitative evaluative, because this this research doing to research a policy or program.   In every stage of the research or retrieval conclusion,do the steps in the form of data reduction, data display, and data verivication. Based on the evaluation of the context, it was concluded that consumer protection policyhas not been formulated clearly, so haven't been     able to understand and be understood  by  Investigating civil servant  (PPNS),  consumer protection Apparatus Builder with regard to consumer  protection as Office of industry and Trading (Perindag) and the Health Service.Based on the evaluation of the input obtained concluded that consumer protection has yet to allocate the funds, facilities and infrastructure, as well as sufficientresources to conduct surveillance of food and drink products as  well as  sweeping  up  food  and drink product containing  coloring  substances forbidden colors  has already circulated in the markets. Based on the analysis of the Evaluation process, the stages that can be obstacles or constraints in the supervision of food and drink products is forbidden color substance is in determining the  time of joint  supervisory with teams BPOM from East Java Province.